Directions of thought for single parents in the EU. Issue 5 (20th October 2021) - Nieuwenhuis, Rense
ABSTRACT: This policy note highlights contemporary research on single parents, and reflects on its implications for social policy developments in the European Union. Three directions of thought are developed regarding single parents' resources, employment and social policies. The aim is to expand the scope of choice among policy alternatives for policy makers. The rise of shared residence urges us to reconsider the gendered nature of single parenthood, considering how to support separated fathers to be involved in their children's life. Employment can come with all kinds of advantages, but earnings are often inadequate for single parents to guarantee a poverty-free existence. With respect to redistributive social policies, single parents' economic position can be heavily affected by policies that are not specifically designed for single parents, or even for families with children. This brings into focus, analogue to gender mainstreaming, the importance of mainstreaming family diversity.